1986
DOI: 10.1177/0148607186010003265
|View full text |Cite
|
Sign up to set email alerts
|

Time Course for the Changes of Serum Lipoproteins and Apolipoprotein T Concentrations after Major Surgical Trauma in Man

Abstract: Trauma induces changes in the serum lipoprotein pattern in man. A characteristic apolipoprotein, named apolipoprotein T existing in its isoforms T-I to T-IV, in the high density lipoprotein (HDL) fraction of serum, also appears in response to trauma. In this report eight patients operated on for abdominal aortic aneurysms were studied concerning the time dependency in changes of serum lipoproteins and the appearance of apolipoprotein T. Blood samples for lipoprotein analysis were taken preoperatively, postoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…During various pathological states, such as trauma, acute infections, myocardial in farctions, and surgery, decreases in TC concentration of a similar magnitude to our study have been reported [17][18][19]. It is not known if the decline in TC has similar underlying physiological mechanisms and may represent a type of response to severe stress.…”
Section: Stress and Lipoproteinsupporting
confidence: 81%
“…During various pathological states, such as trauma, acute infections, myocardial in farctions, and surgery, decreases in TC concentration of a similar magnitude to our study have been reported [17][18][19]. It is not known if the decline in TC has similar underlying physiological mechanisms and may represent a type of response to severe stress.…”
Section: Stress and Lipoproteinsupporting
confidence: 81%
“…Six rats were visually and palpably normal six weeks post surgery and were further used for blood collection (post surgery samples). Collection of blood six weeks post surgery ensures minimal influence of inflammatory, surgical trauma and tissue loss associated changes in serum, since these changes do not persist for more than 5–7 days . No additional drugs or treatment were administered to these rats, except topical application of 5% Povidone Iodine (Wockhardt Health Care) over surgical wound to prevent infection.…”
Section: Methodsmentioning
confidence: 99%
“…Surgery is not just a local tissue trauma but also leads to metabolic and hormonal changes in the organism, which can be designated as postoperative disease or post-aggression syndrome [24 onset of postoperative complications and the patients' reaction to treatment. The observed hypocholesterolemia [25][26][27] is related to reduced LDL amounts, but also a lower level of HDL. Therefore, there is a correlation between the severity of surgical intervention and the rapid reduction of cholesterol-containing lipoproteins in the serum.…”
Section: Cholesterol Comes From Greek (Chole -Bile and Stereosmentioning
confidence: 99%